Pentingnya Pemeriksaan Hemoglobin Pada Ibu Hamil - Lidwina Septie Ch; Margareta Haiti; Novita Anggraini; Mustika Sari; H. Hutabarat (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pregnancy is a physiological condition that is naturally experienced by women who are productive and fertile. During pregnancy, a mother must routinely perform Ante Natal Care (ANC) at least 4 times during pregnancy. The purpose of a mother doing ANC is to maintain the health of the mother and fetus and to prevent complications during pregnancy. One of the causes of complications in pregnant women is anemia due to iron deficiency which is a case that is often found in pregnant women. One indicator of anemia is to look at the picture of hemoglobin levels in pregnant women. One of the causes of anemia is due to iron deficiency which results from insufficient nutrition for pregnant women. The aim of this activity is to screen pregnant women suffering from anemia at RB Sinta and provide education to pregnant women regarding the importance of ANC during pregnancy. Method: This activity is carried out by checking Hb levels in pregnant women and providing counseling